Interaction of Small Zinc Complexes with Globular Proteins and Free Tryptophan. (16th February 2016) - Butkus, Joann M.; O'Riley, Shelby; Chohan, Balwant S.; Basu, Swarna
Abstract : A series of eight water soluble anionic, cationic, and neutral zinc(II) complexes were synthesized and characterized. The interaction of these complexes with bovine serum albumin (BSA), human serum albumin (HSA), lysozyme, and free tryptophan (Trp) was investigated using steady-state fluorescence spectroscopy. Static and dynamic fluorescence quenching analysis based on Stern-Volmer kinetics was conducted, and the decrease in fluorescence intensity of the Trp residue(s) can be ascribed predominantly to static quenching that occurs when the Zn complex binds to the protein and forms a nonfluorescent complex. The role played by the nature of the ligand, the metal, and complex charge in quenching Trp fluorescence was investigated. The binding association constants (K a ) ranged from 10 4 to 10 10  M −1 and indicate that complexes with planar aromatic features have the strongest affinity for globular proteins and free Trp. Complexes with nonaromatic features failed to interact with these proteins at or in the vicinity of the Trp residues. These interactions were studied over a range of temperatures, and binding was found to weaken with the increase in temperature and was exothermic with a negative change in entropy. The thermodynamic parameters suggest that binding of Zn complexes to the proteins is a highly spontaneous and favorable process.